Paradigma dan Revolusi Ilmiah: Analisis Pandangan Thomas Kuhn - LINANDA PUTRI, ELVIRA; KARNELI, YENI; MARSIDIN, SUFYARMA (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This article examines Thomas Kuhn's views regarding scientific paradigms and scientific thinking through in-depth literature analysis. Kuhn's seminal work, "The Structure of Scientific Revolutions" (1962), introduced the concept of paradigm as a framework encompassing the theories, methods, and standards accepted by the scientific community in a particular period. Kuhn's view challenges the traditional understanding of scientific development which is considered linear and cumulative, by introducing the dynamics of scientific revolutions that replace old paradigms with new ones. This article explores key concepts in Kuhn's theory, including normal science, anomalies, crises, and scientific revolutions. Apart from that, the implications of Kuhn's views on scientific methodology and evaluation of scientific research in various scientific disciplines are also discussed. Thus, this article provides comprehensive insight into how scientific change occurs and how scientific thinking is influenced by historical, social, and psychological factors, as well as its relevance in the contemporary scientific context.